2020
DOI: 10.3390/foods9111584
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Propolis Extract as a Natural Antioxidant and Antimicrobial in Gelatin Films Applied to Rainbow Trout (Oncorhynchus mykiss) Fillets

Abstract: Usage of edible films and coatings alone or incorporated with natural extracts are a new approach to preservation and packaging of food. In this study, therefore, the microbiological, chemical quality, and sensorial changes of rainbow trout fillets coated with gelatin films supplemented with propolis extract (PE) (2, 8, 16%), as a source of polyphenols, were determined during 15 days of refrigerated storage (4 ± 1 °C). According to peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 55 publications
5
15
0
Order By: Relevance
“…Similar results were found in studies for chitosan/cinnamon oil and fish gelatine/GL-βCDcurcumin for fresh fish protection (Jouki et al, 2014;Sun et al, 2019). Ucak et al (2020) reported that during the storage period, PB of fillets coated with gelatin films containing propolis were lower than those of the gelatin film coated samples and control samples. The varieties of H 2 S-producing bacteria (Figure 3c), yeast and mold bacteria (Figure 3d), and Pseudomonas spp.…”
Section: Microbiological Qualitysupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were found in studies for chitosan/cinnamon oil and fish gelatine/GL-βCDcurcumin for fresh fish protection (Jouki et al, 2014;Sun et al, 2019). Ucak et al (2020) reported that during the storage period, PB of fillets coated with gelatin films containing propolis were lower than those of the gelatin film coated samples and control samples. The varieties of H 2 S-producing bacteria (Figure 3c), yeast and mold bacteria (Figure 3d), and Pseudomonas spp.…”
Section: Microbiological Qualitysupporting
confidence: 87%
“…Spinelli et al (2015) reported that the sensory quality of fresh fish burgers containing microencapsulated propolis improved. Ucak et al (2020) found similar results. They reported that combining PE with gelatin films had a positive effect on trout fillet.…”
Section: Sensorial Qualitysupporting
confidence: 62%
See 1 more Smart Citation
“…(2020), who found that chitosan coating enriched with lemon peel extract had positive effects on the sensory properties of fillets, and the shelf life extended for 6 days compared with the control. In many studies, it was reported that edible films and coatings incorporated with natural extracts or essential oils could improve the sensory characteristics of fish fillets (Mayeli et al., 2019; Ucak, 2019; Ucak et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…is higher than the findings of the researchers. Ucak et al (2020) reported the numbers of initial total viable, psychrotrophic bacteria, yeastmold and Enterobacteriaceae as 1.543, 1.932, 1.194 and3.390log 10 cfu/g respectively. The findings of the researchers are quite low compared to our findings in terms of total viable, total psychrotrophic bacteria and yeast and mold numbers.…”
Section: Discussionmentioning
confidence: 99%